Alcohol use and self‐perceived mental health status among pregnant and breastfeeding women in Canada: a secondary data analysis. (6th September 2015) - Lange, S; Quere, M; Shield, K; Rehm, J; Popova, S
Abstract : Objective: To estimate the prevalence of alcohol consumption during pregnancy and while breastfeeding in Canada from 2003 to 2010, and to test the relation between self‐perceived mental health status and alcohol consumption during pregnancy and while breastfeeding. Design: Secondary analysis of four cycles of the Canadian Community Health Survey, a population‐based cross‐sectional survey. Setting: Canada. Sample: A total of 18 612 pregnant and 15 836 breastfeeding women. Methods: The prevalence of alcohol consumption during pregnancy and while breastfeeding and 95% confidence intervals (CI) were calculated by province and territory, and cycle. The relation between self‐perceived mental health status and alcohol consumption during pregnancy and while breastfeeding was explored using quasi‐Poisson regression models. Main outcome measures: Alcohol consumption during pregnancy and while breastfeeding, and self‐perceived mental health status. Results: In Canada, between 2003 and 2010, approximately one in every ten pregnant women (9.9%; 95%CI 9.2–10.5%) and two in every ten breastfeeding women (20.3%; 95%CI 19.4–21.2%) women consumed alcohol. Women with a lower self‐perceived mental health status (i.e. 'good') were 1.40 (95%CI 1.18–1.67, P < 0.001) times more likely to have consumed alcohol during pregnancy, compared with women with an 'excellent' self‐perceived mental health. There were no notable differences between the categories of mental health status in regard to alcohol consumption while breastfeeding. Conclusion: Despite public health efforts in Canada, a significant proportion of pregnant and breastfeeding women consume alcohol. It is imperative that a standard screening protocol be initiated among pregnant and breastfeeding women, especially in high‐risk populations (e.g. women utilising substance abuse treatment programs). Tweetable abstract: In Canada in 2003–2010, approximately 10% of pregnant and 20% of breastfeeding women consumed alcohol. Tweetable abstract: In Canada in 2003–2010, approximately 10% of pregnant and 20% of breastfeeding women consumed alcohol.